Aspirin for Evidence-based Preeclampsia Prevention Trial: Effect of Aspirin on Length of Stay in the Neonatal Intensive Care Unit. Issue 1 (March 2019) - Wright, D.; Rolnik, D.L.; Syngelaki, A.; de Paco Matallana, C.; Machuca, M.; de Alvarado, M.; Mastrodima, S.; Tan, M.Y.; Shearing, S.; Persico, N.; Jani, J.C.; Plasencia, W.; et al.
Abstract : ( Am J Obstet Gynecol . 2018;218:612.e1–e6) Preeclampsia is a major cause of maternal and perinatal death and other adverse outcomes for mothers and babies, and has important health care cost implications. Previous studies have found a reduction of the risk of preeclampsia with the use of aspirin. This study aimed to examine the effect of aspirin on the length of stay in the neonatal intensive care unit (NICU), as well as evaluate the impact of screening for preeclampsia and aspirin treatment for high-risk patients on health care costs.